Formation of a waveguide in a LiF crystal by a mid-IR light bullet. (August 2021) - Kuznetsov, A V; Dormidonov, A E; Kompanets, V O; Chekalin, S V; Kandidov, V P
Abstract: We report experimental and numerical investigation of the dynamics of the onset of micromodifications in a LiF crystal upon filamentation of femtosecond mid-IR radiation under conditions of anomalous group velocity dispersion with an increase in the number of acting pulses. It is found that the length of the induced waveguide increases with an increase in the number of acting pulses both in the direction of radiation propagation and in the opposite direction, reaching about 5 mm with an exposure of several thousand pulses. A model is proposed for the waveguide structure formation upon accumulation of changes in the LiF refractive index, caused by the formation of colour centres under conditions of saturation of their concentration. It is shown that the refractive index transverse distribution in the structure has a table-like shape with a diameter of more than 4 μm, which leads to the localisation of radiation reflected from the boundaries of the waveguide.